Հացահատիկի արտադրության պետական կարգավորման ուղիները ՀՀ պարենային անվտանգության ապահովման համատեքստում - Ալեքսանյան, Վ. Ա.; Մատինյան, Ա. Գ.; Շիրոկով, Ս. Ն.; Տրուշկինա, Ի. Ռ. (ՀԱԱՀ հիմնադրամ)
Գյուղատնտեսական արտադրության պետական կարգավորման միջազգային փորձի ուսումնասիրությունը ներկայումս կարևոր նշանակություն ունի Հայաստանի պարենային անվտանգության, մասնավորապես հացահատիկի արտադրության կայունացման, ընդլայնման և ինքնաբավության մակարդակի հետագա բարձրացման առումով։ Վերլուծելով հացահատիկի արտադրության բարելավմանն ուղղված ՀՀ կառավարության 2010-2021 թթ. ֆինանսական աջակցության ծրագրերի արդյունավետությունն ու նպատակահարմարությունը՝ առաջարկում ենք վերանայել պետական կարգավորման գործիքակազմը՝ առաջնահերթություն տալով գնային աջակցությանը և ապրանքային ինտերվենցիային։ Изучение международного опыта государственного регулирования сельскохозяйственного производства в настоящее время имеет важное значение для продовольственной безопасности Армении, в частности для стабилизации, расширения и дальнейшего повышения уровня самообеспеченности зернового производства. В результате анализа эффективности и целесообразности программ финансовой поддержки Правительства РА 2010-2021 гг., направленных на улучшение производства зерна, предлагаем пересмотреть инструменты государственного регулирования, отдавая приоритет ценовой поддержке и товарной интервенции. Food security of the population is one of the main challenges of the 21st century, which, due to the events of recent years (Artsakh war, pandemic, Russian-Ukrainian conflict, sanctions, export restrictions) and their consequences, has become more acute. The stability of the grain sector in the country is of particular importance from the point of view of improving the food security in Armenia. Based on the study of international practice of state support for agricultural production, the results of analysis on the effectiveness of the state support tools traditionally used in different countries, as well as evaluating the state support for the development of grain production in RA, we have developed a model of state regulation of grain production, where the application of a number of realistic methods and measures is emphasized. The results of the studies document that, despite the government’s efforts to expand grain production, the grain sown areas are decreasing year by year, yield growth is not ensured, and the total growth is decreasing. Studying the international experience of state support for agricultural production, analyzing the results of the effectiveness of the state support tools traditionally used in different countries, as well as evaluating the state support for the development of grain production in RA for 2010-2021, we propose to revise the state regulation tools. In particular, to create a grain commission, form a guarantee and collateral price institute, set grain production and distribution quantities, strengthen contractual relations, form a commodity credit company and a grain price stabilization fund, apply commodity intervention, as well as promote economy-infrastructure intervention. We believe that the mentioned fundamental measures will contribute to the prospective development of grain production, ensure realistic results in the medium term, strengthen the cooperation between the state, production and science, as well as increase the self-sufficiency level of grain and, most importantly, will contribute to ensuring the food security of the Republic of Armenia.
Keywords: Ագրարային տնտեսագիտություն և ագրոբիզնես